MAGNETIC-FIELD DEPENDENCE OF THE TRANSPORT CRITICAL CURRENT-DENSITY IN MELT-TEXTURED BI-SR-CA-CU-O HIGH-TC SUPERCONDUCTORS - Kottman, P; Jones, H; Oswald, P; Asplin, S; Grovenor, C (1992)
The transport critical current densities (Jc) in magnetic fields up to 14 T at 4.2 K have been measured on melt-textured Bi-Sr-Ca-Cu-O samples on MgO substrates. The samples were multiphase with partial alignment of the grains. Jc values of 1.58*104 A/cm2, 1.13*104 A/cm2 and 8.2*103 A/cm2were obtained in magnetic fields B=0 T, 1 T and 14 T, respectively. The magnetic field dependence of Jc was relatively flat in fields higher than 1 T. The flux pinning force density increased monotonically in the whole range of fields. The shape of the current-voltage characteristics has been examined and shown to follow approximately a power-law behaviour E approximately Jn in the range of E-values of 10 -4-10-1 V/m with n approximately=30. Preliminary results of Jc(B,T) measurements at higher temperatures are presented.